Development as Consciousness: An Introduction to a New Epistemology. Toward a Logic for Economic Practices - Issa Mansoori (ZBW - Leibniz Information Centre for Economics, 2024)
The main focus of this paper is to propose a new epistemological framework that addresses challenges in the concept of development. Based on the philosophy of mind and consciousness, this framework suggests a practical approach supported by recent scientific findings in different disciplines, including neuroscience. The article explores a new transformation in the development field, departing from dualistic philosophy and the philosophy of language and embracing a new framework of "development as consciousness" with clear and practical implications. Eventually, based on the introduced epistemology, a logic for economic practices is examined based on the new evidence in the real world.
Keywords: 330; Development; Epistemology; Collective consciousness; Intentionality; Economic logic